On-the-fly workload prediction and redistribution in the distributed timed model checker zeus - Braberman, V. (2005)
In this work we present the on-the-fly workload prediction and redistribution techniques used in Zeus [12, 13], a Distributed Model Checker that evolves from the tool Kronos [14]. After reviewing why it is so hard to have good speedups in distributed timed model checking, we present the methods used to get promising results when verifying reachability properties over timed automata [3]. © 2005 Elsevier B.V.